Երգիծական հայ պարբերականները և դաստիարակության հիմնահարցերը - Աղաջանյան, Ռ.
Исследование вопроса сатиры как фактора воспитания имеет теоретическое и, особенно, практическое значение. Рассмотрение сатирической речи как фактора воспитания, в значительной степени способствует целям и содержанию периодики, посвященной сатире, а также исследованию опубликованных карикатур. Ряд произведений армянской юмористической периодики содержат интересный материал для исследования (изучения). The study of the question of satire as a factor of bringing-up has theoretical and mostly practical meaning. We think that considering the humorous speech as a bringing-up factor will be greatly influenced by the study of the purposes and contents of periodicals devoted to the satire and the study of published caricatures as well. A range of Armenian humorous periodicals contain interesting material for studying.
Keywords: Մանկավարժության տեսություն և պատմություն